(untitled) (Bangladesh Journal of Zoology, 2012)
The freshwater gobi, Glossogobius giuris (Hamilton-Buchanan, 1822) (Gobiidae: Perciformes) is an important freshwater fish species in Bangladesh. The age and growth of this species, collected from the river Titas, Brahmanbaria, were studied with transverse sections of otoliths. The otoliths opaque zones that are formed every year were the annual rings. The growth of this species was rapid during the first two years, reaching 18.5 cm in total length. Most of the specimens were 1-2 years old and accounted for 90% in total. The maximum age recorded was five years with 19.5 cm in total length. The von Bertalanffy growth parameters L? and K for this species were 19.58 cm and 1.36/year, respectively. The study indicated that the age and growth of G. giuris can be determined using its sectioned otolith. DOI: http://dx.doi.org/10.3329/bjz.v40i1.12889 Bangladesh J. Zool. 40(1): 13-19, 2012